Spark discharge in megavolt gap initiated by electron beam; Proceedings of the XIth International Conference on Phenomena in Ionized Gases, Prague, 1973 - Elchaninov A. S.; Kovalchuk B. M.; Mesyats G. A. Gennady Andreyevich; Potalisyn Yu. F. (1973, 1973)
В фонде НТБ ТПУ отсутствует